Relación entre el liderazgo transformacional y el desarrollo de equipos de alto rendimiento - Pico, Lucia (2018)
The present study seeks to analyze the main characteristics and relationship that exists between the transformational leadership considered positive towards its followers and the dynamics of looking out for the organization as a whole; Being premise that collaborates in the development of teams of high performance that seek to lead their objectives towards the same end, that is to say, business success. Therefore, it also seeks to develop the aspects that allow management of organizational change through the qualities of the leader within the teams that perform organizational management